"What a nice world“, children’s choir music in secular opus by Stevan Mokranjac - Tasić, Nataša D (Sinteze - časopis za pedagoške nauke , književnost i kulturu, 2015)
Rich choir opus by Stevan Mokranjac also includes compositions for children’s choirs. Similarly to the music written for other types of choirs, the composer gravitated towards both spiritual and secular genres. This paper deals with secular pieces of music, which in Mokranjac’ work mostly means compositions originally intended for children’s choirs, or those personally transcribed by the author. These compositions are grouped in the paper according to the origin of the composer’s inspiration, more specifically, arrangement of folk pieces of music and original work. They are considered in terms of their formal, harmonic and metro-rhythmical analysis, with special attention paid to the consideration of the relation between textual and musical components of individual pieces of music. In addition to such historical-theoretical investigation of Mokranjac’ compositions for children’s choirs, this paper also emphasizes the significance of their presence in the choirs’ repertoire of present time.